Low-carbon energy storage via liquid organic hydrogen carriers: From new developments to global initiatives - Nnabuife, Somtochukwu Godfrey; Hamzat, Abdulhammed K.; Darko, Caleb Kwasi; Udemu, Chinonyelum; Quainoo, Kwamena Ato; Yang, Jinyan; Kuang, Boyu (Elsevier, 2026)
Liquid organic hydrogen carriers (LOHCs) are a promising approach for long-term, low-carbon energy storage via hydrogen, due to their safety profile and compatibility with existing infrastructure. These properties also make it possible for them to efficiently transport and distribute large-scale hydrogen over long distances. This review explores recent advancements in LOHC technology, focusing on innovations that improve hydrogen storage capacity, techno-economics, and environmental impacts of LOHCs. Additionally, it examines global initiatives aimed at scaling LOHC systems for large-scale hydrogen storage and transport whilst highlighting collaborations, policy frameworks, and investment trends that support the integration of LOHC into renewable energy infrastructure. LOHC has the potential to play a critical role in achieving global decarbonization goals by facilitating the safe and reusable storage of low-carbon hydrogen. However, technological challenges persist, and more research is needed to maximize their overall thermal efficiency and market adoption.
Keywords: Liquid organic hydrogen carriers; Energy storage; Hydrogen economy; Low-carbon hydrogen; Hydrogen storage; 34 Chemical Sciences; 3406 Physical Chemistry; 7 Affordable and Clean Energy; 13 Climate Action